2019
DOI: 10.1016/j.dld.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin regulates the fibrogenic phenotype of hepatic stellate cells via c-jun N-terminal kinase activation

Abstract: Background & aims: Myostatin is mainly expressed in skeletal muscle, where it negatively regulates trophism. This myokine is implicated in the pathophysiology of nonalcoholic steatohepatitis, an emerging cause of liver fibrosis. In this study we explored the effects of myostatin on the biology of hepatic stellate cells. Methods: The effects of myostatin were assessed both in LX-2 and in human primary stellate cells. Cell migration was determined in Boyden chambers. Activation of intracellular pathways was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…Whether therapeutic trials aimed at the reduction of the IL-6 activity, such as endurance exercise or anti-IL-6 antibodies, may be beneficial for cancer associated sarcopenia in humans need to be studied further. 47 In the aspect of HCC as the ultimate outcome of liver fibrosis, IL-6 has a profibrogenic role, and myostatin seems to be fibrogenic, 48 while follistatin may attenuate fibrosis, 37 which warrants further studies. There are some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether therapeutic trials aimed at the reduction of the IL-6 activity, such as endurance exercise or anti-IL-6 antibodies, may be beneficial for cancer associated sarcopenia in humans need to be studied further. 47 In the aspect of HCC as the ultimate outcome of liver fibrosis, IL-6 has a profibrogenic role, and myostatin seems to be fibrogenic, 48 while follistatin may attenuate fibrosis, 37 which warrants further studies. There are some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…reported that exercise is effective for improving liver stiffness in patients with NAFLD . Although the causal relationship between exercise and hepatic fibrosis remains unclear, myokines, including myostatin and irisin, are known to be involved in the regulation of hepatic fibrogenesis . As exercise regulates expression of these myokines, exercise might suppress progression of hepatic fibrosis through alterations in myokines.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Although the causal relationship between exercise and hepatic fibrosis remains unclear, myokines, including myostatin and irisin, are known to be involved in the regulation of hepatic fibrogenesis. 38,39 As exercise regulates expression of these myokines, 40,41 exercise might suppress progression of hepatic fibrosis through alterations in myokines. In addition, aging and physical inactivity are associated with inflammation, which causes the progression of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of high myostatin levels being significantly associated with HCC development can be explained by a direct link between myostatin and hepatic fibrogenesis. Myostatin activates a fibrotic progression via C-Jun N-terminal kinase activation or NF-κB-dependent activation: The muscle-liver axis ( Supplementary Figure S1 ) [ 11 , 32 , 33 , 34 , 35 ]. Given that ongoing hepatic fibrosis is an important factor for HCC development [ 36 ], high myostatin levels in high-risk patients activate fibrotic progression and likely play a role in HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preclinical studies showed that myostatin expression was significantly increased in different tumor tissues and could block cancer cell death by regulating mitochondrial metabolism [ 10 ]. Myostatin aggravates hepatic fibrosis through activation of hepatic stellate cells via c-Jun n-terminal kinase activation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%